Differential response of corn and soybean rr crops to exposure to glyphosate and phosphate fertilization Resposta diferencial das culturas de milho rr e soja rr à exposição a glyphosate e adubação fosfatada - Carvalho L.B.* (2015)
© 2015, Sociedade Brasileira da Ciencia das Plantas Daninha. All rights reserved.Phosphorus fertilization can influence the response of glyphosate tolerant crops due to herbicide active absorption is mediated by phosphate carrier. The objective of this research was to analyze growth characteristics of maize RR and soybean RR submitted to spraying glyphosate and application of phosphorus fertilizer. A first experiment was carried out varying glyphosate doses (720 up to 1,440 g e.a. ha-1) and triple superphosphate (54 up to 162 kg P2O5 ha-1) added to the recommended fertilization. A second experiment was carried out varying the same glyphosate doses and with or without phosphorus fertilization (162 kg P 2O5 ha-1). For both crops, plant height and dry mass were influenced by the treatments, while the number of leaves was not affected for both crops. The response of maize and soybean plants, in relation to height and dry mass, was inverse, by spraying glyphosate and applying triple superphosphate; while soybean growth was affected negatively by glyphosate exposure under substrate with high level of phosphorus fertilization (162 kg ha-1 of P 2O5), while maize plant growth increased.